L'altro e lo stesso sulle scene di Performance (1968) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper explores the multiple ways in which the film Performance directed by N. Roeg and D. Cammell almost programmatically builds its narrative on the ideas of performance and performativity themselves. Firstly, in tune with the avant-garde experimentations of the Sixties Performance Art, the film strongly tries to delete the border between representation and reality by mixing actors and no actors and by having its participants profoundly affected by the seemingly ritualistic performance (Turner 1982). Secondly, the film openly attacks any essentialist concept of a unitary identity by exploring, through its ambiguous, even queer characters, the ideas of the double and the androgynous and by deconstructing any ontological discourse built on gender and its performative acts (Butler 1999). Finally, the dysfunctional values enacted by the cinematographic cultural performance align themselves with the counter-cultural ideals of the period by parodying the business-like societal models imposed by the establishment and the obsolete class-based system perpetuated by the English elites. In doing so, it proposes a utopian vision which puts at stake the identity of the nation itself while projecting on film the Sixties revolutionary dream about changing the world.